2015
DOI: 10.1155/2015/376423
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Levels of Melanoma Risk Genes Are Associated with Clinical Characteristics of Melanoma Patients

Abstract: In melanoma development, oncogenic process is mediated by genetic and epigenetic mutations, and few studies have so far explored the role of DNA methylation either as predisposition factor or biomarker. We tested patient samples for germline CDKN2A methylation status and found no evidence of inactivation by promoter hypermethylation. We have also investigated the association of clinical characteristics of samples with the DNA methylation pattern of twelve genes relevant for melanomagenesis. Five genes (BAP1, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 64 publications
(58 reference statements)
1
14
0
Order By: Relevance
“…In this regard, ageing has been described as a major contributing factor to hypermethylation in cancer . Consistent with previous reports, we found DNA methylation differences between acral and nonacral melanomas . Acral melanoma is an uncommon subtype with no association with sun exposure, which occurs frequently in older patients.…”
Section: Discussionsupporting
confidence: 91%
“…In this regard, ageing has been described as a major contributing factor to hypermethylation in cancer . Consistent with previous reports, we found DNA methylation differences between acral and nonacral melanomas . Acral melanoma is an uncommon subtype with no association with sun exposure, which occurs frequently in older patients.…”
Section: Discussionsupporting
confidence: 91%
“…Taken together, these recent reports demonstrate that the pattern of LINE-1 methylation in blood is quite variable, in a clear contrast to tumor samples, which in general exhibit a genome-wide hypomethylation. We have previously reported an apparent contrast between the LINE-1 methylation pattern detected in the blood of patients with melanoma (hypermethylation) and in primary melanomas (hypomethylation) 34. The biological explanation for this discrepancy, and even for methylation differences detected in blood, remains elusive.…”
Section: Discussionmentioning
confidence: 97%
“…As previously discussed, changes in DNA methylation often serve to silence tumor suppressors and have been observed in multiple cancers, including melanoma (de Araújo et al, 2015). To ascertain the effects of treatment on DNA methylation status, we profiled the basal methylome of our cell lines, and DM331 was subjected to the same panel of treatments as performed for gene expression.…”
Section: Plx4720 Treatment Lapatinib Treatment or The Combination Tmentioning
confidence: 99%
“…This indicates that MAPK pathway inhibition or RTK inhibition are insufficient to induce changes in DNA methylation at 8 hours. As with our other analyses of functional genomics data, we were curious to know whether DNA methylation status serves as a marker of sensitivity or synergy in our panel, as other studies had shown that DNA methylation is an effective profiling tool for patient outcome (de Araújo et al, 2015;Conway et al, 2011;Thomas et al, 2014). …”
Section: Plx4720 Treatment Lapatinib Treatment or The Combination Tmentioning
confidence: 99%
See 1 more Smart Citation